Photoacoustic and luminescence characterization of nitrogen heterocyclic aromatic UV-MALDI matrices in solution - Petroselli, Gabriela (2012)
A group of nitrogen heterocyclic aromatic compounds used, among others, as UV-MALDI matrices was studied. By using spectroscopic, luminescence and photoacoustic techniques, as well as time resolved phosphorescence for singlet oxygen production determination, the behaviour of 9-aminoacridine (9AA), 3-aminoquinoline (3AQ), 2-(2-aminoethylamino)-5-nitropyridine (AAN) and 3,4-dihydro-7-methoxy-1-methyl-9H-pyrido[3,4-b] indole (harmaline, HLA) in acetonitrile solutions is described. The results show that for these compounds radiationless processes that release prompt heat to the media are a quite important deactivation mechanism.